A novel preoperative inflammatory marker prognostic score in patients with localized and metastatic renal cell carcinoma - Rishi R. Sekar; Dattatraya Patil; Yoram Baum; Jeffrey Pearl; Anna Bausum; Mehmet A. Bilen; Omer Kucuk; Wayne B. Harris; Bradley C. Carthon; Mehrdad Alemozaffar; Christopher P. Filson; John G. Pattaras; et al. (Asian Journal of Urology)
Objective: Several inflammatory markers have been studied as potential biomarkers in renal cell carcinoma (RCC), however few reports have analyzed their prognostic value in aggregate and in non-clear cell histologies. We hypothesize that a combination of specific inflammatory markers into an RCC Inflammatory Score (RISK) could serve as a rigorous prognostic indicator of overall survival (OS) in patients with clear cell and non-clear cell RCC. Methods: Combination of preoperative C-reactive protein (CRP), albumin, erythrocyte sedimentation rate (ESR), corrected calcium, and aspartate transaminase to alanine transaminase (AST/ALT) ratio was used to develop RISK. RISK was developed using grid-search methodology, receiver-operating-characteristic (ROC) analysis, and sensitivity-specificity trade-off analysis. Prognostic value of RISK was analyzed using the Kaplan–Meier method and Cox proportional regression models. Predictive accuracy was compared with RISK to Size, Size, Grade, and Necrosis (SSIGN) score, University of California-LOS Angeles (UCLA) Integrated Staging System (UISS), and Leibovich Prognosis Score (LPS). Results: Among 391 RCC patients treated with nephrectomy, area under the curve (AUC) for RISK was 0.783, which was comparable to SSIGN (AUC 0.776, p = 0.82) and UISS (AUC 0.809, p = 0.317). Among patients with localized disease, AUC for RISK and LPS was 0.742 and 0.706, respectively (p = 0.456). On multivariate analysis, we observed a step-wise statistically significant inverse relationship between increasing RISK group and OS (all p < 0.001). Conclusion: RISK is an independent and significant predictor of OS for patients treated with nephrectomy for clear cell and non-clear cell RCC, with accuracy comparable to other histopathological prognostic tools.